Cathelicidin Mediates an Anti-Inflammatory Role of Active Vitamin D (Calcitriol) During M. paratuberculosis Infection - Vaccaro, Joseph A.; Qasem, Ahmad; Naser, Saleh A. (Frontiers in Cellular and Infection Microbiology, 2022)
Vitamin D is a key regulator in calcium and phosphorus metabolism which are essential for maintaining bone health. Recent reports also showed a role for vitamin D in immune regulation which may be linked to vitamin D deficiency in autoimmune disorders including inflammatory diseases and Crohn’s disease (CD). This study examines the role of vitamin D deficiency in the regulation of Cathelicidin Antimicrobial Peptide (CAMP) in CD-like macrophages. The latter includes macrophages infected with Mycobacterium avium subsp. paratuberculosis (MAP) isolated from CD patient. Initially, we measured cathelicidin and calcitriol in ex vivo plasma samples from CD patients with or without MAP infection (N=40 per group). We also measured the expression and production of CAMP/LL-37, TNF-α, IL-1β, IL-10, cellular oxidative stress markers, and bacterial viability following treatment of MAP-infected macrophages with four different forms of vitamin D (D2, D3, calcifediol, and calcitriol). From these studies, we determined that LL-37 and calcitriol were significantly lower in CD samples from MAP-positive patients [155.55 ± 49.77 ng/mL and 51.48 ± 31.04 pg/mL, respectively] compared to MAP-negative patients [193.01 ± 78.95 ng/mL and 272.36 ± 94.77 pg/mL, respectively]. Moreover, calcitriol and calcifediol upregulated CAMP expression by nearly 5-fold and 3-fold, respectively. However, following MAP infection, only calcitriol increased CAMP by 3-folds. Both calcitriol and LL-37 reduced intracellular MAP viability by ~3 folds and inhibited TNF-α and IL-1β expression and production in these cells. Treating co-culture of Caco-2 monolayers and MAP-infected macrophages with LL-37 or calcitriol have shown a reduction in NOX-1 expression and DHE signal, in addition to a higher NADPH/NADPt ratio. Notably, calcitriol’s anti-inflammatory effects were lost upon CAMP knockdown by CAMP-siRNA transfection. Altogether, the data indicate that MAP infection and burden is significant in CD by disrupting the conversion of calcifediol to calcitriol and downregulation of CAMP expression leading to vitamin D deficiency.